Living Qur’an; Studi Kasus Tradisi Pembacaan Khotmil Qur’an Pada Air di Pondok Pesantren Nurus Sholah Pamekasan - jatim, jatim; Moh. Bakir (STAI Al-Mujtama Pamekasan, 2025)
This study intends to examine the activities of reading seal of the Quran in water which is believed to be a healing medium. This research is based on the activity of reading seal of the Quran in water at the Nurus Sholah Islamic Boarding School Pamekasan. To answer the focus of the problem in this study, the study used a qualitative approach with the type of field research (field research). Sources of data were collected through observation and interviews. The writing in this study begins by describing the activities seal of the Quran then describes the understanding of community leaders who have a tradition of reciting seal of the Quran on water, and is accompanied by an analysis based on the interpretation of the mufassir of the shifa>' verses relating to the reading seal of the Quran in water. After conducting an in-depth analysis, the findings of this study are that the Nurus Sholah Islamic boarding school believes in the tradition of reading seal of the Quran in water, at the Nurus Sholah Islamic boarding school it is believed that it will become shifa or can cure various physical and spiritual ailments for people who consume the water, because it is believed that there is a blessing from the tradition of reading seal of the Quran in the water. Keywords: Living Qur'an, Seal of the Quran, Water, Shifa>'